Gender representation in economics across topics and time: Evidence from the NBER Summer Institute - Anusha Chari; Paul Goldsmith-Pinkham (Federal Reserve Bank of New York, 2017)
We document the representation of female economists on the conference programs at the NBER Summer Institute from 2001 to 2016. Over the 2013-16 period, women made up 20.6 percent of all authors on scheduled papers. However, there was large dispersion across programs, with the share of female authors ranging from 7.3 percent to 47.7 percent. While the average share of women rose slightly - from 18.5 percent in 2001-04 - a persistent gap between the finance, macroeconomics, and microeconomics subfields remains, with women representing 14.4 percent of authors in finance, 16.3 percent of authors in macroeconomics, and 25.9 percent of authors in microeconomics. We examine three channels potentially affecting female representation. First, using anonymized data on submissions, we show that the rate of paper acceptance for women is statistically indistinguishable from that of men. Second, we find that the share of female authors is comparable to the share of women among all tenure-track professors, but is 10 percentage points lower than the share of women among assistant professors. Finally, within conference programs, we find that when a woman organizes the program, the share of female authors and discussants is higher.
Keywords: A11; A14; J10; J16; 330; gender; economics; representation